Problems of ensuring accuracy installation of building frames - LEPSKA, Liubov (Ways to Improve Construction Efficiency, 2024)
Analysis of the current level of development of the construction industry and trends in the development of technology for the construction of frame buildings for industrial and civil purposes showed the widespread use of frames of one to four floors for commercial, entertainment, office buildings, which determined the list of representative objects for research. These buildings are characterized by high quality of materials and structures used, while the accuracy of assembly has a significant impact on the efficiency of construction, which necessitated the study of the problem of substantiation and achievement of accuracy parameters for the assembly of building frames. From the analysis of the butt joints of prefabricated structures of frame low-rise buildings and the problems of ensuring the accuracy of their installation, it was established that the use of modern butt joints of frame structures allows to significantly increase the efficiency of construction, to improve the quality of buildings, but there are unresolved problems with the formation of sets of assembly equipment for the implementation of assembly methods with restrictions on structures in space and forced methods of landing and fixing structures on supports. The problem of increasing the accuracy of the installation of structures of buildings and structures is considered. The proposed solution to the problem is to improve the installation equipment and the technology of orientation and fixation of structures during their installation. For the automation of the processes of installation of structures, bolted and anchor connections are taken as the main ones as the most technological, which open up the possibility of using semi-automatic devices. The concept of the technological system of frame low-rise residential construction as a holistic, open, organized, adaptive structure of heterogeneous components is substantiated from the standpoint of a general system approach. This allowed us to determine the level of autonomy of the system, its organizational structure and functions, measures to improve adaptability, and an optimization strategy.